(untitled) (Altre Modernità, 2018)
This paper addresses the transmutable nature of London’s cosmopolitan status in 1920s society and culture. It specifically examines the literary and filmic iterations of Wonderful London, which have often been overlooked by historians, juxtaposed with contemporary primary sources. The inter-textual exploration reveals both explicit and implicit ways in which London was depicted as an ideal metropolitan society. I argue that in 1920s British popular culture, a cosmopolitan London was generally perceived as propitious, although fears over miscegenation, immigration and a deeply engrained division between West and East London existed. While contemporary cosmopolitanism was rife with tensions, it was also celebrated and it was a blending of national and international elements that yielded London’s illustrious reputation.